On the life time of contrail cirrus - Schumann, Ulrich; Graf, Kaspar (2012)
Here we present results constraining the mean life time of contrail cirrus based on comparisons of results from a new contrail cirrus model, ECMWF forecast data and several years of Meteosat satellite observations for the North Atlantic and Europe.